2011
DOI: 10.2478/v10172-011-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Fe-Ni-Mo-Cu-B Materials Produced Via Liquid Phase Sintering

Abstract: Sintered materials base on pre-alloyed powders (Fe-Ni-Mo-Cu) are expansively applied in the automotive industry. However, their applications are limited by the particular porosity values of those materials. To reduce the porosity and, simultaneously, to increase the consolidation of sintered alloys, miscellaneous methods within powder metallurgy technologies are utilised, as well as an activated sintering process; for example some boron is added. The boron and iron built a system that is not soluble in any of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…It was found that, in the activated sintering process, the following compounds are formed in the Distaloy SA with 0.6 wt.% B specimen: Fe 2 B, FeMo 2 B 2 , and NiB; while, in the sample made of Distaloy SA with C and B -Fe 2 B, NiB, and Mo 2 B are present. As mentioned in [6,[11][12][13][14][15], the effective role of the borides is to decrease the sintering temperature and increase the amount of liquid phase. It is also to note that, in the samples containing carbon, cementite Fe 3 C is formed.…”
Section: Fig 3 Effect Of Boron On Average Logarithmic Vibration Decmentioning
confidence: 99%
“…It was found that, in the activated sintering process, the following compounds are formed in the Distaloy SA with 0.6 wt.% B specimen: Fe 2 B, FeMo 2 B 2 , and NiB; while, in the sample made of Distaloy SA with C and B -Fe 2 B, NiB, and Mo 2 B are present. As mentioned in [6,[11][12][13][14][15], the effective role of the borides is to decrease the sintering temperature and increase the amount of liquid phase. It is also to note that, in the samples containing carbon, cementite Fe 3 C is formed.…”
Section: Fig 3 Effect Of Boron On Average Logarithmic Vibration Decmentioning
confidence: 99%
“…for the improvement of specific properties like strength, hardness, toughness, frictional and anti-frictional properties, wear resistance, fatigue, etc. [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, no agreement between these 158 results in respect to the magnitude of changes. The shrinkage observed in dilatometric samples was 159 heavily impaired by the evaporation of the boron from the sample surface[22]. Missing boron 160 resulted in creation of smaller amount of eyectic phase.…”
mentioning
confidence: 99%